Marāṭhī samīkshecī vāṭacāla - Kulkarni, Govind Malhar, 1914- (Puṇe : Snehavardhana Pabliśiṅga Hāūsa, 1998)
Study on Marathi criticism.
Mode of access: Internet.
In Marathi.
Keywords: Criticism; Marathi literature -- History and criticism